Levi's will : a novel - Cramer, W. Dale. (Minneapolis, Minn. : Bethany House, 2005)
A family saga spanning three generations, the story follows the life of Will McGruder, who having fled as a young man, seeks to heal the past by bringing his new family to meet his Amish relatives.
Keywords: Amish -- Fiction; Conflict of generations -- Fiction; Inheritance and succession -- Fiction; Domestic fiction; Christian fiction